Ergonomics and Musculoskeletal Health of the Surgeon - Schlussel, Andrew T.; Maykel, Justin A. (Clinics in Colon and Rectal Surgery, 2019)
Surgeons face hazardous working conditions due to ergonomic deficiencies found throughout the operating room. More than 80% of surgeons have succumbed to a work-related injury or illness as a consequence of sustaining awkward or static positions throughout lengthy operations over a career. While the focus of the procedure is directed to the patient, there is little concurrent regard for proper posture or spinal stability. Even when symptoms of discomfort are experienced, they are often ignored. This results in decreased production and may ultimately threaten surgical careers. Surgeons are often unaware of recommendations or guidelines designed to improve their comfort while operating. Furthermore, there is a significant lack of any formal ergonomic education, especially for minimally invasive procedures. Several modifiable risk factors can be adjusted in the operating room to provide a safer working environment. In addition, strengthening, stability, and exercise programs directed by a trained therapist may be employed to improve the surgeon's musculoskeletal health.
Keywords: ergonomics; occupational injury; surgeon health